The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1620/tjem.213.51
|View full text |Cite
|
Sign up to set email alerts
|

Suprailiac or Abdominal Skinfold Thickness Measured with a Skinfold Caliper as a Predictor of Body Density in Japanese Adults

Abstract: Measurement of subcutaneous fat thickness with a skinfold caliper is a simple and inexpensive technique for assessment of body composition, but is influenced by the skin site or the obesity level. The resulting measurement errors may influence the prediction accuracy of body density. We therefore aimed to clarify the characteristics of measurement errors with a skinfold caliper and to determine useful measurement sites for the prediction of body density in Japanese adults of wide-ranging age and obesity levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…A potential reason for our finding that males are more prone to developing PUs is that they have less subcutaneous fat than females. In Japanese adults, a significant gender difference between males and females was found with respect to the amount of subcutaneous fat at all sites except for the side chest and lower back [27]. Given the above, the gender factor may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A potential reason for our finding that males are more prone to developing PUs is that they have less subcutaneous fat than females. In Japanese adults, a significant gender difference between males and females was found with respect to the amount of subcutaneous fat at all sites except for the side chest and lower back [27]. Given the above, the gender factor may require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…High inter- and intra-observer variability, which may result in inaccurate estimates, is perhaps the main reason why skinfold thickness assessment of body fat is not used more widely in population-based research ( 42 ) . However, the only study that included ASF in estimates of reliability found that the influence of measurement errors in skinfold thicknesses was smaller in abdominal and suprailiac skinfolds compared with other sites ( 43 ) . This finding is consistent with our study, in which we found ASF to have higher intra-observer reliability (R %) than other skinfold-thickness site measures and WC, and higher inter-observer reliability than other skinfold sites, although marginally lower than WC.…”
Section: Discussionmentioning
confidence: 99%
“…Skinfold thickness is used in the measurement assuming that subcutaneous fat constitutes a predictable proportion of total body fat. Measurement of subcutaneous fat thickness with a skinfold caliper is an inexpensive and simple technique [11].…”
Section: Introductionmentioning
confidence: 99%